(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: This in vitro study evaluated the influence of luting agents on ultrasonic vibration time for intraradicular cast post removal. MATERIAL AND METHODS: After endodontic treatment, 30 roots of extracted human canines were embedded in resin cylinders. The post-holes were prepared at 10 mm depth and their impressions were taken using autopolymerizing acrylic resin. After casting procedures using a nickel-chromium alloy, the posts were randomly distributed into 3 groups (n=10) according to the luting material: G1- zinc phosphate (SS White) (control group), G2 - glass ionomer cement (Vidrion C; SS White), and G3- resin cement (C&B; Bisco). In G3, the adhesive procedure was performed before post cementation. After 24 h, the cement line was removed at the post/tooth interface using a fine diamond bur, and the ST-09 tip of an Enac ultrasound unit was applied at maximum power on all surfaces surrounding the posts. The application time was recorded with a chronometer until the post was completely dislodged and data were analyzed by ANOVA and Tukey's test (p